Efficiency study of adjustable speed drive with dual motor connection - Anwari, Makbul; Mitsui, C.; Tu, S. (2007)
This paper presents a study of AC adjustable speed drive when used to operate two induction motors. The impact of running the two motors under various loading conditions and operating output frequency to overall efficiency of the adjustable speed drives under room temperature will be discussed. Data obtained from laboratory and their analysis will be presented